2010
DOI: 10.1063/1.3511448
|View full text |Cite
|
Sign up to set email alerts
|

On the velocity variation in atmospheric pressure plasma plumes driven by positive and negative pulses

Abstract: To better understand the variation in the “plasma bullet” velocity, the dynamics of an atmospheric pressure plasma plume driven by positive and negative pulses are investigated in detail. It is found that, before the plasma exits the nozzle, the plasma propagates at a speed of about 30 km/s for both positive and negative pulses. As soon as the plasma exits the nozzle, the plasma propagation speed increases dramatically for both cases. The peak velocity for the case of the positive pulse is much higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
3
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 53 publications
12
38
3
9
Order By: Relevance
“…The reported velocities for ionization waves vary in a wide range of 5·10 3 m/s to 4·10 5 m/s [2,[32][33][34][35][36][37][38][39] which covers the velocities obtained in the present study. Most of the published velocities of the ionization waves have been determined outside of the dielectric tube.…”
Section: Propagation Velocity Of Ionization Wavessupporting
confidence: 83%
See 2 more Smart Citations
“…The reported velocities for ionization waves vary in a wide range of 5·10 3 m/s to 4·10 5 m/s [2,[32][33][34][35][36][37][38][39] which covers the velocities obtained in the present study. Most of the published velocities of the ionization waves have been determined outside of the dielectric tube.…”
Section: Propagation Velocity Of Ionization Wavessupporting
confidence: 83%
“…The reported velocities for ionization waves vary in a wide range of 5·10 3 m/s to 4·10 5 m/s [2,[32][33][34][35][36][37][38][39] which covers the velocities obtained in the present study. According to several studies, the propagation velocity was smaller inside of the tubes and increased at short distance before the ionization wave reaches the exit [31,[42][43][44] and was 2 to 5 times larger outside from the tube. In addition, The velocity of about (1.2-1.6) 10 5 m/s corresponds to the calculated electron drift velocity at electric fields of 10-14 kV/cm which are similar to the measured values in plasma jets [37].…”
Section: Propagation Velocity Of Ionization Wavessupporting
confidence: 83%
See 1 more Smart Citation
“…This speed was maintained almost constant (v s ≈ 89 km/s) for about one centimeter, after which the stream slowed down quickly before dissolving, as the applied voltage decreased to a value of about 4 kV. This acceleration has already been observed, and it has been associated with the diffusion of ionized nitrogen molecules in the helium column [28]. This is in agreement with the emission intensity increase of the N 2 and N + 2 lines that we have observed.…”
Section: Plasma Fast Imagingmentioning
confidence: 93%
“…Jiang et al [122] and Xiong et al [123] did comparative studies on the effects of the polarities of the applied voltages on the propagation of the plasma plumes. They found that the plasma plume is much longer when positive pulsed voltages are used.…”
Section: Effect Of Polarity Of the Applied Voltagementioning
confidence: 99%